A review of the extrapolation method in load spectrum compiling - Wang, Jixin (Strojniški vestnik, 2016)
Load spectrum is the basis of fatigue analysis and life prediction in engineering, and load extrapolation is an essential procedure in determining a long-term load spectrum from a short-term one. Selecting a proper extrapolation method is of great significance when considering various forms and characteristics of load. Over the past few decades, several load extrapolation methods have been proposed, therefore the reasonability and accuracy of a load spectrum extrapolated using different methods should be of great concern. This paper conducts a literature review of commonly used extrapolation methods and proposes some future areas of research. The critical factors, the advantages and disadvantages, and the application ranges of extrapolation methods are summarized using literature and illustrations to provide guidance when selecting a method. In the future, more methods and applications of extrapolation methods will be able to be explored with the further development of statistics and computer software technology.
Keywords: dolgoročni spekter obremenitev; ekstrapolacija obremenitev; kratkoročni spekter obremenitev; kvantilna ekstrapolacija; neparametrična ekstrapolacija; parametrična ekstrapolacija